DESKRIPSI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPAS KELAS 4 SD - Luawo, Sri Devi; Abdullah, Gamar; Isnanto, Isnanto; Kudus, Kudus; Saleh, Meylan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Differentiated learning is an integral part of the curriculum in several schools, including SD Laboratorium UNG, Gorontalo City. One of the subjects taught using a differentiated approach at SD Laboratorium UNG, Gorontalo City is Natural and Social Sciences (IPAS) in grade 4. Based on this, the researcher intends to analyze the implementation of differentiated learning in the subject of IPAS at SD Laboratorium UNG, Gorontalo City. This study focuses on the description of differentiated learning in the subject of IPAS for grade 4 at SD Laboratorium UNG, Gorontalo City. The type of research used is a quantitative descriptive approach. Data collection techniques were carried out through observation, interviews and documentation. The results of the study showed that in the aspect of learning planning, a percentage of 70% was obtained (Good category), which indicates the need for improvement in designing learning strategies that are in accordance with student needs. Solutions that can be applied include teacher training and the provision of teaching materials that support differentiation. Meanwhile, the aspect of learning implementation obtained a percentage of 82.2% (Very Good category), indicating that the implementation has been running effectively. However, to be more optimal and sustainable, implementation needs to supported by more mature and systematic planning. ABSTRAKPembelajaran berdiferensiasi merupakan bagian integral dari kurikulum dibeberapa sekolah, termasuk di SD Laboratorium UNG Kota Gorontalo. Salah satu mata pelajaran yang diampu menggunakan pendekatan berdiferensiasi di SD Laboratorium UNG Kota Gorontalo adalah Ilmu Pengetahuan Alam dan Sosial (IPAS) pada kelas 4. Berdasarkan hal tersebut, peneliti bermaksud untuk menganalisis pelaksanaan pembelajaran berdiferensiasi pada mata pelajaran IPAS di SD Laboratorium UNG Kota Gorontalo. Penelitian ini berfokus pada deskripsi pembelajaran berdiferensiasi pada mata pelajaran IPAS kelas 4 di SD Laboratorium UNG Kota Gorontalo. Jenis penelitian yang digunakan adalah pendekatan deskriptif kuantitatif. Teknik pengumpulan data dilakukan melalui observasi,wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa pada aspek perencanaan pembelajaran diperoleh persentase sebesar 70% (kategori Baik), yang mengindikasikan perlunya peningkatan dalam merancang strategi pembelajaran yang sesuai dengan kebutuhan siswa. Solusi yang dapat diterapkan antara lain pelatihan guru dan penyediaan perangkat ajar yang mendukung diferensiasi. Sementara itu, aspek pelaksanaan pembelajaran memperoleh persentase sebesar 82,2% (kategori Sangat Baik), menandakan pelaksanaan sudah berjalan efektif. Namun, agar lebih optimal dan berkesinambungan, pelaksanaan perlu didukung oleh perencanaan yang lebih matang dan sistematis.